Situation Report: Bulgaria, 20 May 1987 - Radio Free Europe/Radio Liberty Research Institute (RFE/RL Research Institute)
An information bulletin produced by Radio Free Europe/Radio Liberty based on extensive monitoring of communist bloc news outlets and primarily intended for internal circulation. Pieces were generally contributed by the staff of the research and analysis departments and treated current affairs in the region. Todor Zhivkov Elaborates on the Reforms / by Stephen Ashley The Trade Union Congress and "Restructuring" / by Rada Nikolaev Workers to Become "Managers" of Socialist Property / by Rada Nikolaev Reorganization of Cooperatives Announced / by Rada Nikolaev Ivan Panev Appointed First Secretary of Sofia BCP / by Stephen Ashley Dissident Group Appeals to the Vienna CSCE Conference / by Stephen Ashley A John Lennon Cult and Heavy Metal Music Cause Disquiet Measures to Combat the Spread of AIDS / by Stephen Ashley